2014
DOI: 10.1242/jcs.157115
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Sec16 levels and dynamics links proliferation and secretion

Abstract: We currently lack a broader mechanistic understanding of the integration of the early secretory pathway with other homeostatic processes such as cell growth. Here, we explore the possibility that Sec16A, a major constituent of endoplasmic reticulum exit sites (ERES), acts as an integrator of growth factor signaling. Surprisingly, we find that Sec16A is a short-lived protein that is regulated by growth factors in a manner dependent on Egr family transcription factors. We hypothesize that Sec16A acts as a centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 50 publications
6
58
2
Order By: Relevance
“…We have shown that this rate is diminished not only by CDK inhibitors but also, importantly, in starved cells compared to actively proliferating cells. These observations are in line with previous reports showing that the cycling rate of ERES components is under control of growth factors and growth factor‐dependent signaling (Farhan et al , ; Tillmann et al , ). Thus, the activity of the ERES, as measured by their number and by the rate of cycling of COPII and other ERES components, is stimulated under conditions that demand maximal output efficiency from the ER (i.e., during cell proliferation) as they involve cell size increase and organelle expansion.…”
Section: Discussionsupporting
confidence: 93%
“…We have shown that this rate is diminished not only by CDK inhibitors but also, importantly, in starved cells compared to actively proliferating cells. These observations are in line with previous reports showing that the cycling rate of ERES components is under control of growth factors and growth factor‐dependent signaling (Farhan et al , ; Tillmann et al , ). Thus, the activity of the ERES, as measured by their number and by the rate of cycling of COPII and other ERES components, is stimulated under conditions that demand maximal output efficiency from the ER (i.e., during cell proliferation) as they involve cell size increase and organelle expansion.…”
Section: Discussionsupporting
confidence: 93%
“…The endosomal transcriptional regulator RNF11 integrates degradation and transport of EGFR (Farhan et al, 2007;Wendeler et al, 2007;Merte et al, 2010;Sucic et al, 2011). We and others have previously shown a link between EGF ligand stimulation and an adaptation of COP II transport vesicle organization and protein transport through the secretory pathway (Farhan et al, 2010;Simpson et al, 2012;Tillmann et al, 2015). These findings raise the intriguing question of whether EGF ligand stimulation induces the transport of newly synthesized EGFR to the cell surface through changes in the secretory pathway components.…”
Section: Introductionmentioning
confidence: 86%
“…Furthermore, mitogenic stimulation for several hours was shown to increase the levels of Sec16 leading to an increased number of ERES. According to this finding, it was suggested that Sec16 acts as a central node in a coherent feed-forward loop (CFFL) which integrates growth factor signaling and ER export [21]. More recently, it was shown that prolonged stimulation with epidermal growth factor (EGF) also induces the gene expression of several COPII components such as Sec23B, Sec24B, and Sec24D [22] (Fig.…”
Section: Growth Factor Signalingmentioning
confidence: 99%